2011
DOI: 10.1111/j.1552-6909.2011.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Responses of Mothers of Late‐Preterm and Term Infants

Abstract: Objective To compare the emotional responses of mothers of late-preterm infants "(34 0/7 to 36 6/7 weeks gestation) with those of mothers of full-term infants. Design A mixed method comparative study. Setting A southeastern tertiary academic medical center postpartum unit. Participants Sixty mothers: 29 mothers of late-preterm infants and 31 mothers of full-term infants. Methods Measures of maternal emotional distress "(four standardized measures of anxiety, postpartum depression, posttraumatic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 44 publications
9
84
1
8
Order By: Relevance
“…Furthermore, in preterm children whose mother experienced the perinatal period as stressful, the impact of early adversities on behavioural problems and psychiatric disorders at preschool age is greater [30,35,36]. Even mothers of children born late preterm (34-37 weeks gestation) experienced significantly higher levels of emotional stress than mothers of term-born children [26]. Parents of MP children may experience more emotional stress due to worry about the child's health, anxiousness, and depressed feelings, and this may coincide with less attentive or less sensitive parenting [26,37].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, in preterm children whose mother experienced the perinatal period as stressful, the impact of early adversities on behavioural problems and psychiatric disorders at preschool age is greater [30,35,36]. Even mothers of children born late preterm (34-37 weeks gestation) experienced significantly higher levels of emotional stress than mothers of term-born children [26]. Parents of MP children may experience more emotional stress due to worry about the child's health, anxiousness, and depressed feelings, and this may coincide with less attentive or less sensitive parenting [26,37].…”
Section: Discussionmentioning
confidence: 97%
“…As far as we know, combined effects of SES and MP birth on behavioural and emotional problems have not been assessed before. However, prior studies have shown that low SES and preterm birth are both adverse and stressful experiences for children and their parents, [7,16,26,27] for example due to hospitalization at the neonatal intensive care unit [28].…”
Section: Discussionmentioning
confidence: 99%
“…Construct validity has been demonstrated for the state anxiety subscale through concordance with the Anxiety Sensitivity Index (Peterson and Reiss 1987), while strong correlation with both the Anxiety Scale Questionnaire and Manifest Anxiety Scales (Tilton 2008) has provided evidence of concurrent validity for the trait anxiety subscale. This instrument has been successfully used among new mothers of both term and preterm infants (Brandon et al 2011;Dayan et al 2006;Kikkert et al 2010;Neu et al 2014). There is no standard cutoff for referral; however, we used a score of 30 as a threshold to signify elevated levels of anxiety.…”
Section: Psychological Evaluationmentioning
confidence: 99%
“…Third, preterm birth has been associated with adverse mental and physical health of the mother. [42][43][44][45] Poor health of the mother may affect her possibility to foster the child 46,47 and to provide support to the offspring in adulthood, which all may impair the offspring' s ability to fulfill her or his potential. Finally, we cannot rule out that a common genetic basis may underlie the results.…”
Section: Discussionmentioning
confidence: 99%